QUO VADIS RASIONAL CHOICE DALAM PILKADA ACEH BARAT MENUJU 2017 - Alimas Jonsa (Universitas Teuku Umar, 2016)
The title of this study is Quo Vadis Rational Choice in the Election Aceh Barat in 2017. The reason for choosing such title was because the election western district of aceh in 2017 so unique and diverse calonnya will start of a candidate backed by national party, local party and the independent. But in this case researchers want to assess fenomen what is mean by quo vadis rational choice in for the section kabupataen aceh barat. Social phenomenon in behavior choose quo vadis rational choice in local election district of aceh western in transition toward democracy in 2017 in determining voting. Methods used in this research is a method of the qualitative study, where needed was an understanding of social phenomena, so as to become the focus of major is acquire understanding of at the action and meaning social trend in the viewing angle the subject of research. While type research used in this research was descriptive qualitative research. Descriptive research done with intent provides an overview of certain social trend which exists in the community with using patterns of inductive think that is the way of thinking this to be of the particulars to general in terms of audience.Keywords: Quo Vadis, Rational Choice, Election, Aceh Barat